Scar endometriosis: an uncommon surgical aftermath - Pathade, Sumedha; Panchbudhe, Shruti; Deshmukh, Prasad; Nayak, Arun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Endometriosis is a benign condition wherein endometrial tissue lies outside the uterine cavity. Abdominal scar endometriosis is a rare entity following pelvic surgeries caused as a result of deposition of endometrial tissue at scar site. Patient usually presents with triad of presence of mass over scar site, cyclical pain during menses and bleeding. Histopathological examination remains gold standard for diagnosis in which the presence of endometrial glands, stroma and hemosiderin laden macrophages can be seen. We presented a case of 35 years old lady with history of caesarean section done 3 years back who came with complaints of swelling over the scar site and cyclical pain with tenderness present over lump. Ultrasonography revealed presence of firm mass which was removed by wide local excision and histopathology confirmed the diagnosis of scar endometriosis.